Pegaruh Saluran Distribusi Terhadap Volume Penjualan (Studi Pada Pt Graha Kerindo Utama Kediri) - Nurul Farida (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2016)
In streamlining of product and service flow from produsers toconsumers one of the most important or should not be ignored isdistribution, in an effort to reach the purpose and target of company inmarketing every companies do distribution. The main purpose of companyin essence is same, that is increasing the volume of sale so the provit willbe increasing without ignoring consumers satisfaction.This research usingthe quantitavestatistics with “Analis Korelasi Sederhana-- often called“Korelasi Pearson (Person Product Moment), it purpose for knowing theeffect of distribution on volume of sales. Based on the result obtained bycorrelation r= 0,987 and do experiment of “t-- with the result tb=19.42 so itcan be concluded based on t tabe, t greater than t in table a= 1% (19.42 >3,169), so Ho was rejected. It mean between distribution with volume ofsales is very influential and significant.